O ESTUDO NAS REPRESENTAÇÕES SOCIAIS DOS ALUNOS CONCLUINTES DO ENSINO FUNDAMENTAL - Koga, Viviane Terezinha (2012)
This investigation consists of a study on the social representations of elementary school 9th grade students. It was carried out in three State schools in Ponta Grossa – PR, two of which achieved good IDEB results whereas the performance of the third was below average. Due to the low performance the students have in external evaluations, such as SAEB and PISA, poor study habits and the increasing lack of interest in studying, besides constant complaints from teachers about this situation, the aim of the investigation was: a) to reveal social representations of students in the 9th grade about studying; b) to present the confront of social representations of studying in schools of higher and lower IDEB results; c) to analyze deeply social representations of studying in the school with the lowest IDEB score. This research is quali-quantitative, with a pluri-methodological approach. It is based on the Social Representations Theory, proposed by Moscovici and co-workers; and, in special, the structural approach and the concepts of autonomy and heteronomy, according to Piaget. Data collection was carried out in two phases which corresponded to the application of a questionnaire (N=213) in the three schools and the interviews (N=40) in the lowest IDEB score school. The data was analyzed aided by the software SPSS, EVOC, SIMI and ALCESTE, as well as by the content analysis. Results indicated that: a) the 9th grade students have an ambivalent social representation of studying: sometimes it is seen in a positive way, as something important for the future, others negatively, described as boring and tiring; sometimes it appears that the positive representation is characteristic of the lowest IDEB school, and the negative one is present in schools with higher IDEB score; b) students answers reveal that the IDEB good results are a consequence of the school control mechanisms, longer hours dedicated to studying and lower failure rates; c) most students said they did not have studying habits; d) in the higher IDEB score schools, students opted for more memorization alternatives and study control, in the lowest IDEB score school the most chosen alternative was study elaboration.